Two Oxime Derivatives Including Succinimid and Morpholin Groups - Dincer, Muharrem; Ozdemir, Namik; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Int Union Crystallography, 2005)
[Abstract Not Available]
Keywords: crystal structures; organic molecule; drug action